Konstruksi Makna Friend with Benefit (FWB) di Kalangan Mahasiswa Kota Malang dari Tinjauan Fenomenologi Sosial - Lintang Razita Zafarani; Megasari Noer Fatanti (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
Friends with Benefit (FWB) is an interpersonal relationship that only promotes mutually beneficial activities for actors. The FWB phenomenon is often carried out by students in Malang City. According to the BKKBN, 80% of people in Malang are married due to pregnancies outside of marriage (KTD). Therefore, researchers are interested in studying the phenomenon of the FWB relationship among students in Malang City. This study aims to determine the construction of meaning and the process of interpreting the FWB relationship among students in Malang City. This study uses a phenomenological approach with the theoretical framework of Peter L. Berger which focuses on the process of individual social construction of reality. There are six informants in this study. Data analysis is used through several stages, namely, data collection, data reduction, data presentation, and verification and drawing conclusions. From the results of this study, it was found that the meaning of the FWB relationship was not only limited to sexual activity, but there were other meanings. Other meanings, such as a friend to talk to entertain themselves, a friend for a walk or even just doing lecture assignments. The other findings that were found were worries and fears when undergoing FWB relationships. The concerns and fears referred to in terms of the FWB relationship being lived are known by partners and even other people and the fear of contracting HIV/AIDS.